THU0019 Onset AGE Influences Clinical and Laboratory Profile of Patients with Systemic Lupus Erythematosus. (10th June 2014) - Monticielo, O.A.; Gasparin, A.A.; Hendler, J.; Chakr, R.; Moro, A.L.; Hax, V.; Zanchet, D.; Siqueira, I.; Palominos, P.E.; Brenol, C.; Kohem, C.; Xavier, R.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem inflammatory autoimmune disease with higher prevalence among women [1]. The first manifestation of SLE occurs most commonly at childbearing age, but can appear at any age [2]. Previous studies demonstrated heterogeneous clinical presentation, medication use and disease severity among different onset age groups [3]. The influence of age at disease onset on the clinical presentation and prognosis remains not well recognized. Objectives: The present study aims to evaluate differences in clinical and laboratory manifestations and medication use in each SLE patient group according age of onset disease. Methods: This cross-sectional study consisted of 549 patients with SLE who attended the Rheumatology Clinic of the Hospital de Clínicas de Porto Alegre between 2003 and 2013. Interview during medical consultation and medical chart review were used to collect demographic, clinical and laboratory data. The patients were classified into three groups according to their ages at disease diagnosis. Results: Among the 549 patients studied, 54 (9.8%) were Juvenile-onset (≤16 years), 427 (77.8%) were Adult-onset (>16 and <50 years) and 68 (12.4%) were Late-onset (≥50 years). The frequency of women was higher in Adult-onset (93.9%) than in Juvenile-onset (83.3%) (p=0.003). Arthritis was predominantly found in Adult-onset group (79.1%) when compared with Late-onset (61.8%) (p=0.006). Nephritis was more common in Juvenile-onset (66.7%) than in Late-onset (27.9%) (p<0.001), as also occurred with positive results for anti-DNA (64.2% vs. 38.1%, respectively). A non-significantly difference of Sjögren's syndrome, antiphospholipid syndrome, concomitant autoimmune disease and family history of SLE was observed among the groups. Disease activity index and damage scores were similar among the groups. The Juvenile-onset was more likely to require oral corticosteroids (p=0.01), pulse methylprednisolone (p<0.001), cyclophosphamide (p<0.001), azathioprine (p<0.001) and mycophenolate mofetil (p<0.001) in the treatment and maintenance of SLE than the other two groups. In contrast, the Late-onset had used more commonly hydroxychloroquine than the Juvenile-onset (98.5% vs. 90.6%, respectively) (p=0.04). Conclusions: Our findings confirm most of the data previously published. The juvenile-onset group showed a more severe disease due to the higher incidence of nephritis and the need of a more aggressive treatment with immunosuppressive drugs. The rate of women is bigger in the adult-onset group, which can be explained by the hormonal effect of estrogen. References: Manson JJ, Isenberg DA. The pathogenesis of systemic lupus erythematosus. Neth J Med. 2003 Nov;61(11):343-6. Rothfield N. Clinical features of systemic lupus erythematosus. In: Textbook of Rheumatology, Kelley WN, Harris ED, Ruddy S, Sledge CB (Eds), WB Saunders, Philadelphia 1981. Brunner HI, Gladman DD, Ibanez D, Urowitz MD, Silverman ED. Difference in disease features between childhood-onset and adult-onset systemic lupus erythematosus. Arthritis Rheum. 2008 Feb;58(2):556-62. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4193